PENGGUNAAN ALAT PERAGA SEDERHANA UNTUK MENINGKATKAN KETERAMPILAN MATEMATIKA SISWA - Sugiarti, Lana; Ningsi, Gabariela Purnama; Jeramat, Eufrasia (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mathematics is one of the subjects that students are rarely interested in. The material in mathematics lessons is also abstract. So that most students find it difficult to understand mathematics. Therefore, a tool is needed in understanding mathematical material so that students have no difficulty in learning the problem. One of the tools or media that can be used to help students is by using teaching aids. Props used in community service activities include the mean, median, and mode boards; number line integer arithmetic operations; corner clock; and the number plate to the power of two. This community service activity was carried out in the Tenda study group, Ruteng. The duration of this activity is 3 months. The method used in this mentoring is to use the method of demonstration, discussion, question and answer and the practice of using teaching aids. The results of community service carried out are students feel helped in understanding mathematics subject matter and students feel happy because they experience fun learning. Students also find it easier to understand mathematics subject matter which is indicated by the scores obtained by students when working on practice questions related to mathematics material through the questions given by the community service team which has increased and students are enthusiastic in working on practical questions using math teaching aids. Thus, it can be concluded that community service activities through the use of teaching aids have succeeded in helping students overcome difficulties in understanding mathematics.